PENGEMBANGAN KAMUS VISUAL UBARAMPE MANTU ANDROID SEBAGAI MEDIA PEMBELAJARAN BAHASA JAWA SMA - Pratiwi Beta Wardani; Joko Sukoyo (Jurnal Education and Development, 2023)
According to interviews with students and teachers at SMA Negeri Karangpandan, the lack of ubarampe mantu vocabulary knowledge among students is a barrier to learning Javanese. Therefore, it is necessary to develop media in the form of an Android application for the ubarampe mantu visual dictionary. This study aimed to describe the needs of students and teachers for the ubarampe mantu visual dictionary android application, develop a prototype of the application, and describe the results of the validation test and acceptance test of the application. This study follows the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Interviews and annotated bibliographies were used to collect data for this study, while descriptive qualitative analysis was employed to analyze the data. According to the findings of this study, students and teachers require media in the form of an Android-based ubarampe mantu visual dictionary. Using Microsoft PowerPoint, iSpring Suite 10, JavaScript 8, and Website 2 APK Builder Pro 3.0.2, media prototypes can be created. The results of the media validation test were rated "good" and "very good," whereas the results of the material validation test were rated "good enough," "good," and "very good." Students and teachers can also receive the Android application ubarampe mantu visual dictionary as a learning tool. Therefore, media products can be utilized as learning media.